Effects of Breast Cancer Counseling on Attitudes of Acting Mothers in BSE in Timpag Village, Kerambitan Subdistrict, Tabanan Regency, Bali-Indonesia - Ni Wayan Sukma Adnyani; Ni Putu Diah Andini (Journal of Midwifery, 2019)
This study aims to determine the effect of breast cancer counseling on the attitude of mothers doing BSE actions. The study design used a pretest-posttest model to measure the knowledge and attitudes of 45 respondents. Data from research results were collected using a questionnaire and data analysis using the Rank Wilcoxon statistical test. The results showed: (1) Before giving counseling, knowledge included as many as 34 categories (75.56%), 9 categories as enough (20.00%), and 2 categories as good (4.44%), while attitudes included negative categories were 32 (71.11%) and positive categories were 13 (28.89%). (2) After being given knowledge counseling including as many as 3 categories (6.67%), sufficient categories as many as 5 (11.11%), and good categories as many as 37 (82.22%), while attitudes including negative categories as much as 4 ( 8.89%) and positive categories as much as 41 (91.11%). The Wilcoxon test with a p value of <0.05 was said to have a difference, namely the value of p = 0,000, and the value of Z count - 5,393 which means that there is an effect of breast cancer counseling on the attitude of mothers doing BSE in Timpag Village.